Deteksi Kerawanan Banjir Genangan Menggunakan Topographic Wetness Index (TWI) di Sub Das Way Katibung - Ma’rufah, Wahyuni; Ridwan, Ridwan; Amin, Muhammad (Jurnal Agricultural Biosystem Engineering, 2024)
This research aims to detect flood susceptibility using the Topographic Wetness Index (TWI) and create a flood susceptibility map in the Way Katibung Sub-watershed using the Topographic Wetness Index (TWI). This study employs the Topographic Wetness Index (TWI) method with observation parameters including land slope, soil type, land elevation, rainfall, and land use. The results show that the most influential parameter on the Topographic Wetness Index (TWI) is the land slope. Therefore, TWI can be used to detect flood susceptibility in the Way Katibung Sub-watershed, which is predominantly flat. Areas with the lowest average TWI value of 6.35 have no potential for flooding, whereas areas with average TWI values of 10.94 and 13.95 are the most susceptible to flooding. The flood-prone areas are primarily located near river streams, such as Mekar Sari, Sumber Agung, Talang Way Sulan, Karang Pucung, Banjar Sari, Purwodadi, and Pamulihan in Way Sulan District. Keywords: Flood Puddle, Sub-DAS Way Katibung, TWI, Vulnerability.